Granaries used in maize storage and conservation across agroecological zones in the Republic of Benin: distribution, characteristics and associated postharvest losses - Fassinou Hotegni, Nicodeme V.; Agbo, Natacha F.M.; Salaou, Mouizz A.B.; Odjo, Sylvanus; Bokonon-Ganta, Aimé H.; Achigan-Dako, Enoch G. (Elsevier, 2024)
Maize is the major staple food grown and consumed by Sub-Saharan African population. Despite government efforts to increase maize production, huge postharvest losses are recorded, with increased hunger and food cost. Granaries constitute for many farmers the safest and most economical way to store their crops. In this study, we investigated the diversity, distribution and structural characteristics of granaries used for maize storage and conservation across Benin agroecological zones as well as the factors that determine postharvest losses of maize in the Republic of Benin. In total, 345 households were surveyed in five agroecological zones (AEZ) based on a structured interview. Qualitative and quantitative data including sociodemographic parameters, granary characteristics, maize grain conservation forms, and postharvest losses associated with different granaries were recorded. Descriptive statistics were used to characterize both granary types and conservation methods across AEZ. To establish associations between farmers' conservation methods and granary types, Factorial Analysis of Correspondence (FAC) was performed. The factors influencing maize postharvest losses were investigated using a multiple linear regression analysis. Results showed six types of granaries classified into two main groups: Agoh, Avah, Akah, and Loumourè made of plant materials and Dibo and Bourarou made of clay. The granary type used was AEZ and socioethnic group dependent and was also function of the conservation method used by farmers. Granaries in southern AEZ were more prone to losses than those in the northern zone. The regression model showed that agroecological zone, education level, granary type, conservation method and maize storage form influenced the losses in maize production as perceived by farmers. This study highlights the need for extension agents and decision-makers to improve and adapt approaches used in postharvest loss management based on granaries structures characteristics and efficiency, local climate and accessibility of building materials within farmers' surroundings.